Molecular engineering of Ni–/Co–porphyrin multilayers on reduced graphene oxide sheets as bifunctional catalysts for oxygen evolution and oxygen reduction reactions. Issue 9 (6th July 2016) - Sun, Jiqing; Yin, Huajie; Liu, Porun; Wang, Yun; Yao, Xiangdong; Tang, Zhiyong; Zhao, Huijun
Abstract : Ni– and Co–porphyrin multilayers on reduced graphene oxide (rGO) sheets are reported as novel bifunctional catalysts for the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). Abstract : Ni– and Co–porphyrin multilayers on reduced graphene oxide (rGO) sheets are reported as novel bifunctional catalysts for the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). After binding with organic porphyrin molecules, the catalytically-active Ni 2+ and Co 2+ ions are periodically constructed onto the rGO surfaces via the layer-by-layer (LBL) assembly technique. The resulting catalysts exhibit good performance towards both OER and ORR, which is achieved with accurate control of the composition and thickness of the multilayer structures. This work highlights the potential for the fabrication of efficient electrocatalysts via molecular design.